Prevalence of pulp stones in IOPA radiographs - Sudarsan Ravichandran; Jayanth Kumar Vadivel (Wolters Kluwer Medknow Publications, 2022)
The presence of calcifications or hard deposits within the pulp chamber of the teeth is referred to as pulp stones. There is a geographic and ethnic variation in the occurrence of these calcifications in the population. The article assessed the occurrence of pulp stones. As a secondary objective, the gender or age difference was also assessed. This study was carried out retrospectively by analyzing the archived dental radiographs. A total of 100 radiographs were taken for the analysis based on random sampling. The selected samples were scanned for the occurrence of pulp stones. From a total of 100 subjects, 15% had more than one pulp stone. This study revealed the prevalence of dental stones in the sample population was low. However, of the teeth examined, the mandibular arch had a higher incidence when compared to the maxillary arch. No significant correlation was found among gender or age. Further studies on a larger scale are required to find possible associations that would help determine clinical outcomes.